Implementation of Blockchain Technology in Strengthening the Sharia Economy: An Analysis from the Maqāṣid al-Sharī’ah Perspective - fitri fitri (Institut Studi Islam Muhammadiyah Pacitan, 2026)
The rapid development of digital technology has significantly transformed contemporary economic systems, including the implementation of Islamic economic practices. One of the most prominent technological innovations is blockchain, which offers transparency, security, decentralization, and efficiency in transaction management. This study aims to analyze the role of blockchain technology in strengthening Islamic economics from the perspective of Maqāṣid al-Sharī‘ah. This research employs a qualitative approach using library research by examining scholarly journals, books, regulatory documents, and authoritative reports related to blockchain and Islamic economics. The findings indicate that blockchain has substantial potential to support Islamic economic development, particularly in Islamic financial institutions, zakat and waqf management, smart contracts, and halal supply chains. The characteristics of blockchain align with the objectives of Shariah, especially in protecting wealth (ḥifẓ al-māl), promoting transparency, and ensuring justice in economic transactions. However, the implementation of blockchain in Islamic economics also faces several challenges, including regulatory uncertainty, limited technological literacy, and differing scholarly opinions regarding digital assets and smart contracts. Therefore, a comprehensive Shariah-based governance framework and collaboration among regulators, practitioners, scholars, and technology experts are essential to ensure that blockchain adoption remains consistent with Islamic principles and effectively contributes to public welfare (maṣlaḥah).